The Relationship between Hba1c Levels and Body Mass Index with Severity of Diabetic Neuropathy - Rauf, Muhammad; Sari, Masyita (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Diabetic neuropathy is the most common microvascular complication in diabetes mellitus patients. Diabetic neuropathy is known to be associated with conditions of hyperglycemia and obesity that occur in diabetic patients. Hyperglycemia in diabetic patients can be monitored through HbA1c levels. This study aimed to assess the relationship between HbA1C values and body mass index with the severity of diabetic neuropathy based on nerve conduction velocity examination. Methods: A study with a cross-sectional design with a total of 25 subjects with diabetes mellitus. The severity of diabetic neuropathy was determined based on Baba's diabetic neuropathy classification (BDC), degrees 0 to 4. In all study subjects, plasma HbA1c levels were examined, and body mass index was assessed. The relationship between categorical variables was tested with the chi-square test, and the relationship between numerical and categorical variables with a one-way ANOVA test, the value was considered statistically significant if the p-value <0.05. Results: The 25 subjects with diabetes found a mean age of 54.88 (±SD 8.918) years, with a gender distribution of 46.4% for women and 42.9% for men. The average HbA1c level was 8.9560 (± 2.21850), and the highest body mass index was obese (50%). There was a significant relationship between HbA1c levels and the severity of diabetic neuropathy based on electrophysiological examination (p<0.05), but there was no significant relationship between the value of body mass index and the severity of diabetic neuropathy. Conclusion: Increased HbA1c levels are associated with increased severity of peripheral neuropathy in patients with diabetes mellitus.